Persistent Carrier Status Of Ehrlichiosis And Babesiosis In A German Shepherd Dog After Clinical Recovery - P.I.Ganesan (The Indian Veterinary Journal, 2023)
Vector- borne diseases of canines are common all over the globe and their prevalence is high in India due to the hot and humid climatic conditions. Among prevailing vector- borne diseases canine ehrlichiosis, babesiosis and hepatozoonosis are commonly reported, followed by anaplasmosis and trypanasomiasis. A seven months old German shepherd male dog brought to the VeterinaryClinical Complex of Apollo College of Veterinary Medicine, Jaipur. The clinical signs exhibited by the dog were anorexia for 45days, congested mucus membrane, transient fever, and enlarged popliteal lymphnode. The dog was treated in various clinics using cefotaxime and other supportive drugs without success.Dog infested withRhipicephalus sanguineous was confirmed. Blood smear ex amination revealed a mixed infection of E.canis and B.bigemina on zero day of admission. Hematological tests revealed alterations in the haemogram. Accordingly, the dog was treated with single dose of diminazeneaceturate on first day, followed with Doxycycline for a period of 14 days and the dog recovered from the clinical signs. The body weight of the dog increased 1.5 kg during this treatment period and the dog was in normal habits. Blood smear examination of the dog on 26th and 32nd day post treatment confirmed the presence of both B.gibsoni and E.canis showing  the resilience status for B.gibsoni and E.canis parasites after the treatment regimen,  denoting  persistent carrier status of both B.gibsoni and E.canisin the infected dog.